EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MENGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA KELAS III SD NEGERI 01 PUCUNGKIDUL TULUNGAGUNG - Sri Fitri Rahayu; Zainuddin, Mohammad Riza (LPPM STAI Muhammadiyah Probolinggo, 2024)
Islamic religious education is the most important lesson for students who are still at elementary school level, where the material is material for understanding the basics of the Islamic religion, at which time students are directed to strengthen their spiritual and noble morals. The aim of Islamic Religious Education lessons in schools is to grow, develop and improve their faith through providing and cultivating students' knowledge, appreciation and practice of Islamic religious teachings. In other words, it is hoped that students will be able to practice correctly and understand the basics of the Islamic religion which they will apply in their daily lives. This means that this material must be conveyed to students well and effectively. So that the material is conveyed well and effectively and can be understood by students, and they are interested in learning Islamic Religious Education, one way is to choose the right learning media. Therefore, the main problem in this study is how effective Islamic religious education learning is in elementary schools. This research proves that there is the effectiveness of audio visual media for learning Islamic Religious Education.